Drug Use and Life Chaos as Potential Factors Contributing to HIV Viral Load among People with Lower Health Literacy. (4th February 2021) - Kalichman, Seth C.; Kalichman, Moira O.; Banas, Ellen; Hill, Marnie; Katner, Harold
Abstract: Background: Lower health literacy is associated with poorer health outcomes in people living with HIV (PLWH), but the explanatory mechanisms for these associations are not well understood. Factors such as drug use and life chaos may at least in part account for the relationship between lower health literacy and poor health outcomes. The current study tested the hypothesis that lower health literacy would predict drug use, which in turn would predict life chaos, and that all three factors would be related to poorer heath, defined by higher concentrations of HIV viremia. Methods: Patients receiving HIV care ( N = 251) at an HIV clinic in the southeastern United States completed computerized interviews and permission to access their medical records. Process modeling tested direct and indirect effects of all variables in a serial mediation model. Results: The direct effects of lower health literacy and drug use were significantly related to HIV viremia. In addition, the indirect effect of health literacy on HIV viremia through drug use was significant. However, results did not demonstrate any effect, direct or indirect, of life chaos on HIV viremia. Conclusion: Findings from this study bolster previous research demonstrating lower health literacy and drug use as barriers to HIV care, and show that lower health literacy impacts HIV viremia, at least in part, through drug use. Interventions aimed to improve HIV treatment outcomes in lower health literacy populations may be enhanced by integrating evidence-based approaches to reducing drug use.